Humanitarian Engineering: a proposal to articulate engineering education with social issues (2019)
The academy has focused on theoretical discussions that distance themselves from real social and economic issues of the communities. Aiming to create synergy between engineering education and low-income communities, the School of Exact Sciences and Engineering of Sergio Arboleda University has focused on Humanitarian Engineering. This study seeks to establish the first model used in the design of the first academic offer of this approach: a course where students must face challenges of communities and design artifacts, systems or engineering processes under social, environmental and technical constraints. A framework is established for Humanitarian Engineering, followed by a case study where the proposed course model is analyzed through students and teachers’ perceptions after its implementation. The proposed changes for a second version of the course are concluded.